2020
DOI: 10.1128/aem.03038-19
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of NADH Dehydrogenase Mutants Reveals Flexibility and Limits of Pseudomonas taiwanensis VLB120’s Metabolism

Abstract: Obligate aerobic organisms rely on a functional electron transport chain for energy conservation and NADH oxidation. Because of this essential requirement, the genes of this pathway are likely constitutively and highly expressed to avoid a cofactor imbalance and energy shortage under fluctuating environmental conditions. We here investigated the essentiality of the three NADH dehydrogenases of the respiratory chain of the obligate aerobe Pseudomonas taiwanensis VLB120 and the impact of the knockouts of corresp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…P. putida has both NDH‐I and NDH‐II, while the NDH‐I is typically the major complex . This was observed for Arabidopsis , where the respiration rate was inhibited by rotenone for the first 4 h and then progressively recovered to initial levels within 32 h. Similar internal compensation of NADH dehydrogenase activity was also confirmed for P. taiwanensis VLB120, a strain that shares 98.9 % genome similarity with P. putida . Nevertheless, the results confirmed the inhibition of rotenone on NADH dehydrogenase activity and consequently confirmed the active role of NADH dehydrogenase in the EET route.…”
Section: Resultssupporting
confidence: 57%
“…P. putida has both NDH‐I and NDH‐II, while the NDH‐I is typically the major complex . This was observed for Arabidopsis , where the respiration rate was inhibited by rotenone for the first 4 h and then progressively recovered to initial levels within 32 h. Similar internal compensation of NADH dehydrogenase activity was also confirmed for P. taiwanensis VLB120, a strain that shares 98.9 % genome similarity with P. putida . Nevertheless, the results confirmed the inhibition of rotenone on NADH dehydrogenase activity and consequently confirmed the active role of NADH dehydrogenase in the EET route.…”
Section: Resultssupporting
confidence: 57%
“…The highest reported glucose uptake rate for P. taiwanensis VLB120 of 10 mmol gCDW -1 h -1 (Rühl et al, 2009) translates into a maximal product synthesis rate of 0.6 gMK gCDW -1 h -1 and a NAD(P)H turnover of 52 mmol gCDW -1 h -1 . While this is about 2-fold the rate under standard growth conditions (at a specific growth rate of 0.68 h -1 (Nies et al, 2020)), this demand does not challenge the redox cofactor regeneration capacity of P. taiwanensis VLB120 reported to reach 149 mmol gCDW -1 h -1 (Rühl et al, 2009). These in silico analyses indicate a substantial room for improvement of methyl ketone synthesis in P. taiwanensis VLB120 by metabolic engineering.…”
Section: Metabolic Modeling Predicts Genetic Engineering Targets For mentioning
confidence: 93%
“…Optimization of the redox metabolism, such as redox cofactor engineering, shown to be important for methyl ketone production in E. coli, was not pursued. We argue that the high flexibility of Pseudomonas to balance redox cofactors (Kohlstedt and Wittmann, 2019;Nies et al, 2020;Nikel et al, 2016) renders such elaborate engineering efforts superfluous. Moreover, the performed in silico analysis showed that the capacity of the strain for methyl ketone production has not been fully exhausted and can be increased further by metabolic engineering.…”
Section: Discussionmentioning
confidence: 99%
“…While this is about 2-fold the rate under standard growth conditions (at a specific growth rate of 0.68 h -1 (Nies et al, 2020)), this demand does not challenge the redox cofactor regeneration capacity of P. taiwanensis VLB120 reported to reach 149 mmol gCDW -1 h -1 (Rühl et al, 2009). These in silico analyses indicate a substantial room for improvement of methyl ketone synthesis in P. taiwanensis VLB120 by metabolic engineering.…”
Section: Metabolic Modeling Predicts Genetic Engineering Targets For Improved Methyl Ketone Productionmentioning
confidence: 93%